2016
DOI: 10.18533/rss.v1i8.51
|View full text |Cite
|
Sign up to set email alerts
|

Assessing public participation in water conservation and water demand management in water stressed urban areas: Insights from the City of Gweru, Zimbabwe

Abstract: <p>The paper investigates the level of water user participation in water conservation and demand management in Gweru. Data was solicited from a combination of user opinion and key informants selected from the local authority and citizen representative groups. A household survey including 489 residents was carried out in the different categories of residential areas in the city. Several water conservation and demand management measures were identified. However compliance with the measures was poor. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The study findings of Diakite & Amadou, (2020) in Mali reported that many respondents were aware of WCPs but had low participation in conservation practices. The study by Kusena et al, (2016)in Zimbabwe assessing public participation in water conservation found that only a few respondents participate in conserving water due to limited involvement in decisionmaking and conservation practice literacy. Also, though this paper did not concentrate on the determinants of household participation in WCPs, the descriptive results on parameters related to the theory of planned behaviour, which includes individual attitude, social membership, and perception, indicate less than 40% of the respondents had a good attitude and perception towards WCPs, suggesting that in the study area there is little emphasis on socialpsychological factors to influence pro-environmental behaviours as proclaimed by (Ajzen, 1991) and (Bosnjak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study findings of Diakite & Amadou, (2020) in Mali reported that many respondents were aware of WCPs but had low participation in conservation practices. The study by Kusena et al, (2016)in Zimbabwe assessing public participation in water conservation found that only a few respondents participate in conserving water due to limited involvement in decisionmaking and conservation practice literacy. Also, though this paper did not concentrate on the determinants of household participation in WCPs, the descriptive results on parameters related to the theory of planned behaviour, which includes individual attitude, social membership, and perception, indicate less than 40% of the respondents had a good attitude and perception towards WCPs, suggesting that in the study area there is little emphasis on socialpsychological factors to influence pro-environmental behaviours as proclaimed by (Ajzen, 1991) and (Bosnjak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Preventing water pollution, efficient water use, water recycling or reuse, water supply, and demand management centralise the discussion of water conservation (MoW-URT, 2002).Though engineering-based solutions have been applied to optimise water supply and demand, recently, household and community participation has also been identified as a good approach to conserving this scarce resource (Kusena et al, 2016).…”
Section: Household Participation In Conserving Water Resourcesmentioning
confidence: 99%